ANALISA JUMLAH PRODUKSI PADA INDUSTRI RUMAH TANGGA DENGAN MENGGUNAKAN LOGIKA FUZZY: STUDI KASUS UD TEMPE PUJI KECAMATAN BAYANG KABUPATERN PESISIR SELATAN - Putra, Ondra Eka; Febrianti, Eka Lia (IAIN Batusangkar, 2016)
Total production of a company must be appropriate to the existing demand and supply, if the amount of production is not suitable then it would result in losses of the company because there is no analysis of the market needs for demand and supply of products. UD Tempe Puji is domestic industry that produces tempe every day to provide the needs of the market. In producing UD Tempe Puji only estimate the market needs are uncertain that the market needs are not being met or exceeded. In the analysis of the amount of production at UD Tempe Puji using Tsukamoto fuzzy logic so that the amount of tempe to be produced in accordance with market needs based on demand and supply that exist automatically. Data was analyzed based on the demand, supply and production quantities are never done by UD Tempe Puji. In the method of drawing conclusions fuzzy Tsukamoto, each consequent upon the rule should be represented by a set of fuzzy with the membership function monotonous, as a result, the output results of inference of each rule is given explicitly by ?-predicate, the final result is obtained by using a weighted average.